Interculturality in peace-building and mutual edification (Rm 14:19) - Jean-Claude Loba Mkole (HTS Teologiese Studies/Theological Studies, 2019)
This article shows that, according to Romans 14:19, peace-building and mutual edification are closely interrelated. This hypothesis is substantiated through an intercultural method, which explores the issues of peace from a triple perspective: a contemporary culture (DR Congo), an original Biblical culture (Rm 14:19) and a past Church culture (Church Fathers). These three frames basically agree that for restoring and maintaining peace, it is important to fight against its main cause, namely sin. It is equally important to cultivate things that promote peace and mutual edification.